Dietary administration of tetrodotoxin and its putative biosynthetic intermediates to the captive-reared non-toxic Japanese fire-bellied newt, Cynops pyrrhogaster. (October 2017) - Kudo, Yuta; Chiba, Chikafumi; Konoki, Keiichi; Cho, Yuko; Yotsu-Yamashita, Mari
Abstract: The origin of tetrodotoxin (TTX) in amphibians has long been disputed. In this study, TTX and its putative biosynthetic intermediates or shunt compounds (4, 9-anhydro-10-hemiketal-5-deoxyTTX and Cep-242) were dietary administered to the captive-reared, non-toxic Japanese fire-bellied newt, Cynops pyrrhogaster . After 4 weeks, the ingested compounds were detected mainly in the newt body using liquid chromatography-mass spectrometry (LC-MS), while these compounds were not converted into other TTX analogues in newts. Highlights: Tetrodotoxin (TTX) and its related compounds were dietary administered to the newt. TTX was detected mainly in the body of the newt 4 weeks after administration. TTX and its related compounds in the tested newt were hardly secreted for 4 weeks. Administered compounds were not converted into other analogues in the newt.